Radiation-induced acute toxicities after image-guided intensity-modulated radiotherapy versus three-dimensional conformal radiotherapy for patients with spinal metastases (IRON-1 trial): first results of a randomized controlled trial = Radiogene Akuttoxizität nach bildgeführter intensitätsmodulierter Strahlentherapie versus dreidimensionaler konformaler Strahlentherapie bei Patienten mit Wirbelkörpermetastasen (IRON-1 trial) - Sprave, Tetyana; Verma, Vivek; Förster, Robert; Schlampp, Ingmar; Bruckner, Thomas; Bostel, Tilman; Welte, Stefan Ezechiel; Tonndorf-Martini, Eric; El-Shafie, Rami; Nicolay, Nils; Debus, Jürgen; Rief, Harald (Strahlentherapie und Onkologie, 2018)
PURPOSE: Radiation therapy (RT) provides an important treatment approach in the palliative care of vertebral metastases, but radiation-induced toxicities in patients with advanced disease and low performance status can have substantial implications for quality of life. Herein, we prospectively compared toxicity profiles of intensity-modulated radiotherapy (IMRT) vs. conventional three-dimensional conformal radiotherapy (3DCRT). - METHODS: This was a prospective randomized monocentric explorative pilot trial to compare radiation-induced toxicity between IMRT and 3DCRT for patients with spinal metastases. A total of 60 patients were randomized between November 2016 and May 2017. In both cohorts, RT was delivered in 10 fractions of 3Gy each. The primary endpoint was radiation-induced toxicity at 3 months. - RESULTS: Median follow-up was 4.3 months. Two patients suffered from grade 3 acute toxicities in the IMRT arm, along with 1 patient in the 3DCRT group. At 12 weeks after treatment (t2), 1 patient reported grade 3 toxicity in the IMRT arm vs. 4 patients in the 3DCRT group. No grade 4 or 5 adverse events occurred in either group. In the IMRT arm, the most common side effects by the end of irradiation (t1) were grade 1-2 xerostomia and nausea in 8 patients each (29.6%), and dyspnea in 7 patients (25.9%). In the 3DCRT group, the most frequent adverse events (t1) were similar: grade 1-2 xerostomia (n= 10, 35.7%), esophagitis (n= 10, 35.8%), nausea (n= 10, 35.8%), and dyspnea (n= 5, 17.9%). - CONCLUSION: This is the first randomized trial to evaluate radiation-induced toxicities after IMRT versus 3DCRT in patients with vertebral metastases. This trial demonstrated an additional improvement for IMRT in terms of acute side effects, although longer follow-up is required to further ascertain other endpoints.